Individual incentives in program participation: splitting up the process in assignment and enrollment - Andrea Maria Weber (Institute for the Study of Labor (IZA), 2008)
In this paper we investigate two stages in the process that leads to participation in ALMP programs. We use unique administrative data from the Austrian unemployment registers which allow us to distinguish between caseworker assignment and actual program enrollment. Although 25% of newly unemployed workers are assigned to a program, only half of them enroll and participate in the program longer than 5 days. This difference between assignment and enrollment rates cannot be explained by job entries, program cancelations, or rejected program applications alone. Therefore we analyze the influence of observable characteristics on each stage of the participation process. We find that beside policy regulations individual worker incentives play an important role in determining program participation.
urn:nbn:de:101:1-2008032063
Keywords: J24; 330; Unemployment; active labor market policy; evaluation; Arbeitslosigkeit; Arbeitsmarktpolitik; Arbeitsuche; Bildungsverhalten; Ökonomischer Anreiz; Österreich